2016
DOI: 10.1371/journal.pone.0163957
|View full text |Cite|
|
Sign up to set email alerts
|

Within-Site Variation in Feather Stable Hydrogen Isotope (δ2Hf) Values of Boreal Songbirds: Implications for Assignment to Molt Origin

Abstract: Understanding bird migration and dispersal is important to inform full life-cycle conservation planning. Stable hydrogen isotope ratios from feathers (δ2Hf) can be linked to amount-weighted long-term, growing season precipitation δ2H (δ2Hp) surfaces to create δ2Hf isoscapes for assignment to molt origin. However, transfer functions linking δ2Hp with δ2Hf are influenced by physiological and environmental processes. A better understanding of the causes and consequences of variation in δ2Hf values among individua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 54 publications
0
16
0
Order By: Relevance
“…However, the role of plumage in sexual selection or intrasexual communication in this species is not known, and the inconsistent sex effect in our study suggests that it may be more complicated than female-choice sexual selection. It should also be noted that the geographic location of molt could be stochastic for individuals of the same population from year to year (Pyle et al 2009, Nordell et al 2016, so molt may not necessarily always occur at this stopover site.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the role of plumage in sexual selection or intrasexual communication in this species is not known, and the inconsistent sex effect in our study suggests that it may be more complicated than female-choice sexual selection. It should also be noted that the geographic location of molt could be stochastic for individuals of the same population from year to year (Pyle et al 2009, Nordell et al 2016, so molt may not necessarily always occur at this stopover site.…”
Section: Discussionmentioning
confidence: 99%
“…at or near breeding and overwintering sites). However, there is increasing evidence that molt can also occur during migratory stopover, or after movement to specific ''molting grounds, '' in a variety of taxa (''moltmigration''; e.g., Salomonsen 1968, Leu and Thompson 2002, Reed et al 2003, Pyle et al 2009, Quinlan and Green 2011, Lourenço and Piersma 2015, Nordell et al 2016, Pillar et al 2016. For instance, several passerine species in western North America, such as the Bullock's Oriole (Icterus bullockii; Pillar et al 2016) and Black-headed Grosbeak (Pheucticus melanocephalus; Siegel et al 2016), pause their southward migration to wintering areas in the monsoon region of northwestern Mexico to complete prebasic molt.…”
Section: Introductionmentioning
confidence: 99%
“…An interaction between year and other sources of variation has been found in some studies, with species-specific (Nordell et al 2016) and age (Gow et al 2012;Haché et al 2012) effects being different among years. Most studies have not investigated differences between sexes, but those that did have been inconclusive (Langin et al 2007) or found no effect (Nordell et al 2016). A further assumption is that δ 2 H f values should not vary between feather types in the same individual, but small differences have been found between primary and rectrix feathers in a songbird (Haché et al 2012) and large differences were seen between various primary feathers in a raptor (Meehan et al 2003).…”
mentioning
confidence: 91%
“…Specifically, δ 2 H f can vary among individuals of different ages (Meehan et al 2003;Langin et al 2007;Gow et al 2012;Haché et al 2012), and between years at the same site (Haché et al 2012;Van Dijk et al 2014;Tonra et al 2015). An interaction between year and other sources of variation has been found in some studies, with species-specific (Nordell et al 2016) and age (Gow et al 2012;Haché et al 2012) effects being different among years. Most studies have not investigated differences between sexes, but those that did have been inconclusive (Langin et al 2007) or found no effect (Nordell et al 2016).…”
mentioning
confidence: 99%
See 1 more Smart Citation